FISHES OF DOYANG RESERVOIR, NAGALAND - ODYUO, N. SUBENTHUNG; NAGESH, T. S. (Journal of the Inland Fisheries Society of India, 2021)
Reservoir fisheries is becoming a vital component of inland fishery resources of India with potential not only to enhance the country’s inland fish production but also in providing food and nutritional security to the people and opportunities for livelihood and employment. Unlike rivers, which are under increasing threat of environmental degradation, reservoirs offer ample scope for fish yield optimisation through effective management (Vass, 2009). Reservoirs are human-engineered habitats that occur in almost all major river basins. The fish fauna is recruited to the reservoir from their riverine antecedents (Prasad, 1919; Fernando and Juraj, 2007). Indian reservoirs show rich ichthyofaunal diversity Sugunan (1995), which represents the parent river system. On the basis of studies conducted prior to 1995, large reservoirs, on an average, harbour 60 fish species of which at least 40 species contribute to the commercial fisheries (Sugunan, 1995).